Impact of Waqf Property at Primary to Higher Islamic Educational Institutions in Bangladesh: A Study - Islam, Mohammad Saiful; Rahman, Md. Masudur (Indonesian Journal of Law and Society, 2024)
Since the arrival of Islam in the Indian subcontinent, the waqf has been playing a vital role in spreading the spirit of Islam. It is a Muslim's religious endowment to a religious, educational, or charitable cause. It is also an ongoing charity (Sadaqah Jariyah). Muslims, inspired by the Prophet Muhammad (p.b.u.h.) and his traditions, offer their belongings and property in the name of Allah in order to please the Almighty Allah and find peace in the afterlife. Since the early days of Islam in the Indian Subcontinent, the waqf property has developed social, educational, economic, health, and many other philanthropic organizations throughout Bangladesh. The importance of educational institutions stands out among hundreds of waqf institutions. People donate generously to teach and promote Islamic knowledge and institutions. In most situations, waqf property results in the preaching and promotion of Islam, as well as the production of practicing Muslims and Islamic philosophers. Thousands of Islamic educational institutions, mosques, maktabs, and hospitals have been formed as charitable organizations in the country's different localities through the asset of waqf. The majority of waqf properties are managed by locals. People have been inspired for centuries to expedite such endowments around the country. The paper focuses on how the waqf property plays an important role in Islamic educational institutions and how it affects the people and society of Bangladesh.